2020
DOI: 10.14447/jnmes.v23i3.a01
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Electrospinning of Polymer Nanofibers: History and Main Applications

Abstract: Electrospinning is an intensely facile methodology for the precise manufacturing of polymer nanofibers by manipulation of electrostatic force, which stunts like a driving force. In this technique, fibers produced with a diameter range between 50 to 500 nm. Two practices are made up by the scientists for electrospinning of versatile polymer. Polymers can be electrospun into ultrafine fibers in solvent solution or melt form. Tremendous progress had been made in this field in the past, and numerous applications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 93 publications
(115 reference statements)
1
13
0
Order By: Relevance
“…In addition, Polyvinyl alcohol (PVA) is a biocompatible and highly hydrophilic semicrystalline polymer with excellent properties such as strength, water solubility, gas permeability, and thermal stability characteristics [11] . Nanofiber fabrication using PVA based precursors through electrospinning technique has been extensively studied since in the 15th century for the preparation of ultrafine separation filters, biodegradable mats, and inorganic fibres [12] .…”
Section: Hardware Descriptionmentioning
confidence: 99%
“…In addition, Polyvinyl alcohol (PVA) is a biocompatible and highly hydrophilic semicrystalline polymer with excellent properties such as strength, water solubility, gas permeability, and thermal stability characteristics [11] . Nanofiber fabrication using PVA based precursors through electrospinning technique has been extensively studied since in the 15th century for the preparation of ultrafine separation filters, biodegradable mats, and inorganic fibres [12] .…”
Section: Hardware Descriptionmentioning
confidence: 99%
“…The nanofibers is deposited onto the collector and expelled after 1-hour of Electrospinning. The nanofibers are left to dry at room temperature for a few hours, to allow the evaporation of residual solvent [12].…”
Section: Electrospinning Processmentioning
confidence: 99%
“…Thus, researchers have attempted to modify EPS into beneficial materials, one of which is nanofiber membranes prepared using an electrospinning method with various solvents such as N , N -dimethylformamide (DMF), d -limonene, cyclohexane, 1,2-dichloroethane, tetrahydrofuran, dichloromethane, and N , N -dimethylacetamide . Electrospinning is a method of fiber spinning that utilizes electrified polymers, both in solution and in melt form . Several studies have confirmed that electrospinning is one of the most economical, simple, and facile methods for fabricating nanofibers. Moreover, this technique allows the modification of the size, morphology, and composite formation of the fibers with other materials to enhance membrane functionalization .…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a method of fiber spinning that utilizes electrified polymers, both in solution and in melt form . Several studies have confirmed that electrospinning is one of the most economical, simple, and facile methods for fabricating nanofibers. Moreover, this technique allows the modification of the size, morphology, and composite formation of the fibers with other materials to enhance membrane functionalization . Rajak (2020) synthesized an electrospun EPS nanofiber membrane using a DMF solvent for application in air filters, which demonstrated that EPS nanofiber membranes have a high air filtration efficiency of approximately 99.99% .…”
Section: Introductionmentioning
confidence: 99%